Mapping out the scenarios of ocean energy scale-up based on the development of offshore wind [version 2; peer review: 1 approved, 4 approved with reservations] - Benjamin Lehner; Anne-Caroline Pillet; Hinne van der Zant; Simon Stark (Open Research Europe)
Background Our oceans remain one of the last untapped large sources of renewable energy. The predictability and reliability of marine energy technologies could contribute significantly to the global energy transition. By 2022, marine energy, and in particular wave and tidal energy have reached a pre-commercial phase in their development. Methods This study investigates the potential progression of the wave and tidal energy sector in the next three decades based on the offshore wind sector in the past three decades. Two different models were developed from the yearly capacity increase of offshore wind in Europe and applied to the wave and tidal energy sector. Results According to both models, the 40 GW 2050 target for marine energy set by the European Commission in 2020 could be reached if European coastal countries, including countries associated to the EU-27, adopt supportive policies for both technologies immediately. A sensitivity analysis shows further that a small delay right now will have tremendous negative impacts on fulfilling the EU goals and the contribution of marine energy to the energy transition. Conclusions The ocean energy sector shows a strong growth potential and is capable of supporting the European and global climate targets substantially by 2050. Lessons learned from the offshore wind sector can help scope and support the growth of marine energy technologies.